PROBLEM BASED LEARNING MODEL ON THE ABILITY OF STUDENTS MATHEMATICAL CONNECTION - Julyanasari, Nining; Praja, Ena Suhena (PRISMA, 2019)
Mathematics is one of the subjects that are interrelated, both in mathematics and outside mathematics. So the ability is important mathematical connections controlled by the learner. Learning model that can improve students' mathematical connection that is the model of Problem Based Learning (PBL). Based on this background, the purpose of this study is to determine the activity of students in learning by using the PBL model, knowing the increase in students' mathematical connection capabilities on each indicator and overall, knowing the increase in students' mathematical connection capability significantly, knowing the individual and classical completeness of the ability of students' mathematical connections, determine a student's response to the application of PBL models. The method used in this study is the experimental method the population of all class X SMAN 1 Astanajapura academic year 2014/2015. The sampling technique used technique purposive sampling The results showed that (1) An increase in the activity of students using the PBL model (2) An increase in the ability to connect mathematical students on each indicator and overall (3) An increase in the ability to connect significantly with the value  (4) the achievement of individual mastery with  and 1,095,and classical completeness with  and  (5) the existence of a positive response to learning PBL models. Based on the results obtained are expected research further research can use the PBL model transform and determine the increase math skills.Keywords: Problem Based Learning, Student Mathematical Connections